Kultura polityczna elit w miastach partnerskich pogranicza Polski, Słowacji, Węgier i Ukrainy - Agata Nijander‑Dudzińska (Ksiegarnia Akademicka Publishing, 2014)
The Influence of the Twinning on the Political Culture of Urban Elites on Borderland of Poland, Slovakia, Hungary and Ukraine (research concept)